Giant Congenital Melanocytic Naevus with Proliferative Nodules Mimicking Congenital Malignant Melanoma: A Case Report and Review of the Literature of Congenital Melanoma. (16th January 2013) - Scalvenzi, Massimiliano; Palmisano, Franco; Cacciapuoti, Sara; Migliaro, Fiorella; Siano, Maria; Staibano, Stefania; Tornillo, Luigi; Costa, Claudia
Abstract : Congenital malignant melanoma (CMM) is a rare condition that is defined as malignant melanoma recognized at birth. CMM may develop in utero in one of three ways: (1) transmission by metastasis through the placenta from a mother with melanoma; (2) primary melanoma arising within a giant congenital melanocytic naevus (GCMN); (3) primary de novo cutaneous CMM arising in utero. CMM can be confused clinically and histologically with benign proliferative melanocytic lesions such as giant congenital nevi. We describe the case of a patient presenting a GCMN with proliferative nodules, clinically and dermoscopically resembling a CMM, demonstrating the importance of caution in making a diagnosis of MM and highlighting the possibility that benign lesions as GCMN can mimic a malignant melanoma in this age group.